Ultrasound Imaging Improves Identification of Prominent Hardware in the Surgical Treatment of Distal Radius Fractures: A Cadaveric and Prospective Clinical Study - Watchmaker, Jacqueline D.; Daley, Roger A.; Watchmaker, Greg P.; Grindel, Steven I. (Journal of Wrist Surgery, 2016)
Background Volarly applied locking plates are one of several current treatment options for displaced fractures of the distal radius. Presently, surgeons use intraoperative depth gauges and fluoroscopy to select and confirm proper screw length. The contour of the dorsal cortex beneath the extensor compartments along with fracture comminution may limit the accuracy of screw length selection.Question/Purpose To evaluate the accuracy of ultrasound (US) and fluoroscopy in the detection of dorsally prominent screws placed during volar plating of experimentally created distal radius fractures and extend this prospectively into the clinical setting.Patients and Methods Distal radius fractures were experimentally induced in fresh cadaveric arms. The fractures were then internally fixated with volar locking plates utilizing fluoroscopic imaging. US imaging of the dorsal surface of the radius was then performed followed by dorsal dissection and direct caliper measurements to quantitate screw tips as recessed, flush, or protruding from the dorsal cortex. A small, prospective clinical study was also conducted to validate the clinical usefulness of using US to provide additional information regarding screw tip prominence.Results Our study demonstrated that US was able to detect dorsally prominent screw tips not visible on fluoroscopy. Cadaveric dissection showed a higher statistical correlation between US imaging and actual prominence than between fluoroscopy and actual prominence.Conclusions US examination after volar plate fixation of comminuted distal radius fractures may detect dorsal screw tip prominence when screw lengths are selected to engage the dorsal cortex.Level of Evidence IV
Keywords: distal radius; fracture; fluoroscopy; ultrasound; volar plate